Local Environmental Stewardship and Restoration of Wetlands in Uringu Ecological Zone, Meru county,Kenya. - Kubaison, Dr. Simon Thiane (Meru Universty of Science and Technology International Conference (MUSTIC), 2025)
Although Meru county is one of the most forested counties in Kenya, there are environmental concerns in the northern part of the county(Nyambene) including conflicts between people living downstream and those who are upstream when water is on a limited supply, especially during the months of September and October. There is also interference by individuals who use the water resource in a manner that infringes on the right of others to derive benefits from the river(NEMA,2020) The purpose of the study was to explore local environmental stewardship efforts being employed for protection of the diversity of wetland habitats, flora and fauna within Uringu ecological zone.The study explored factors that are enabling or inhibiting the success of environmental stewardship. Environmental stewardship is one way through which people get involved in promoting sustainability. Strategies of wetland restoration included public awareness on importance of conservation and proper land use practices,reporting to authorities incidents of environmental degradation practices and law enforcement in deterring environmental pollution.The study carried out interviews through a focus group method with 65 members of Kieiga Conservation SHG,a local CBO involved in environmental conservation within Uringu ecological zone. The study focused on restoration of two types of wetland through afforestation of Kieiga forest, which forms part of Nyambene ranges.The 10 year old afforestation project focused on restoring rivers and swamps.Ecosystem benefits derived from the wetland includes Provision of domestic water, fish,fodder, reeds/papyrus, thatch and organized water supply projects. The study observed that well managed wetlands improve water quality as well as serving as important nursery and breeding areas for animals, fish and birds.Wetlands also serve as a good Source of food such as fish and rice. They further provide habitat for various animal and plant species such as antelope,birds and other water fowls. The study further observed that two springs that had dried up prior to the reforestation project were now restored and some members of the neighbouring community had harvested piped water for their homes. Members were asked to indicate their perception on the benefits accrued from the restored forest.On a likert scale of 1-5 the responses yielded the following results: A source of animal grazing and watering points( mean of 4.2),source of fuel and building materials (4.1), domestic water supply (4.68)),Research and education (3.3),recreational and aesthetic sites for bird watching, hunting, and fishing(3.8) Key challenges and threats to wetlands identified in the study include encroachment for settlement and agriculture ,pollution, Over-exploitation of wetland goods and services and other human land degradation practices. The study identified key factors that influenced members to take the conservation initiative. Desire to protect water sources and access quality water got an acceptance rating of 82%.Reforestation was another attraction at 68%.creation of habitat for animal and bird species(63%).Restoration of degraded lands 65%.recreation and aesthetics 60%.Childhood experiences 64%.Access to forest products such as Wood fuel 60%.Earning a living through contracts provided by government agencies and contracted service providers(71%). The study recommends Construction of water pans by local CBOs to store storm water in order to create more watering points,Encourage appropriate and sustainable land uses that can be easily supported by the fragile environment,Promote water and soil conservation measure to curb soil erosion.and reclamation of river banks through restoration of indigenous trees. Key Words:environmental stewardship,wetland restoration, Sustainable land use.